Experimental Mathematics. Volume 15, Number 3, 2006 - A K Peters (A K Peters, 2009)
Investigations of Zeros near the Central Point of Elliptic Curve L-Functions Full TextPDF (418.7 KB) Author Steven J. Miller 257-279